Assessment of auditory and vestibular function and gene therapy in the Snell’s waltzer mouse model of human deafness and balance dysfunction - Eyal Marton; Roni Hahn; Lior Bikovski; Gwenaëlle S. G. Géléoc; Jeffrey R. Holt; Matti Mintz; Karen B. Avraham (Mammalian Genome, 2026)
Abstract The Snell’s waltzer mouse ( Myo6 sv/sv ) serves as a model for human deafness and vestibular behavioral impairment, caused by a spontaneous 130 bp recessive deletion in the Myo6 gene. In this study, we characterized the auditory and vestibular phenotypes of Myo6 sv/sv mice. These mice exhibit profound hearing loss, with cochlear hair cell stereocilia beginning to fuse soon after birth, ultimately leading to disorganization of hair bundles and degeneration of hair cells. Mice also exhibit behavioral phenotypes characterized by severe imbalance, hyperactivity with bouts of circling, and delayed spatial learning of a novel environment, but preserved normal behavioral circadian rhythms. These behaviors emerge in association with the loss of the characteristic staircase morphology of vestibular hair cell stereocilia soon after birth and the subsequent profound elongation of the stereocilia. Adeno-associated virus (AAV) gene replacement therapy, delivered on the day of birth or one day after, failed to restore auditory or vestibular function. Our findings underscore the essential role of Myo6 in the auditory and vestibular systems and imply prenatal intervention may be required for effective therapy.